Pengaruh Kualitas Produk dan Harga Terhadap Keputusan Pembelian Produk Sari Roti di Kampung Cisadaria - Muhamad, Irgi; Halim, Hartanto; Herlina, Ellin (Lembaga Pendidikan dan Penelitian Manggala Institute, 2025)
This study aims to measure the effect of product quality and price partially and simultaneously on purchasing decisions for Sari Roti products, with a case study of consumers in Kampung Cisadaria. The results showed that the regression equation obtained was Y = 0.5613 + 0.511 X1 + 0.300 X2. Partially, each variable (product quality and price) influences purchasing decisions, as evidenced by the t-count which is greater than the t-table and a significance value of less than 0.1. Simultaneously, the product quality and price variables also influence purchasing decisions, with an F-count value of 218.145 which is greater than the F-table of 3.108 and a significance value of 0.000. Based on the determination coefficient test, the R-square value partially influences product quality by 79.2% and price influences by 60.5% partially. And based on the determination coefficient test, the adjusted R-square value obtained was 83.8%, while the remaining 16.2% was influenced by other factors not examined in this study. Based on the results of this study, it can be concluded that product quality has a fairly large influence compared to price. Therefore, companies need to pay more attention to determining the price of Sari Roti products. For example, by conducting a survey of the average economic conditions of the community before determining the price of Sari Roti products.